Tracheotomy care simulation training program for inpatient providers. Issue 5 (5th September 2022) - Tiu, Ryan Alyson‐Yao; Meyer, Tanya Kim; Mayerhoff, Ross M.; Ray, Joel C.; Kritek, Patricia A.; Merati, Albert Lincoln; Sardesai, Maya Guirish
Abstract: Objectives: Tracheotomy complications can be life‐threatening. Many of these complications may be avoided with proper education of health care providers. Unfortunately, access to high‐quality tracheotomy care curricula is limited. We developed a program to address this gap in tracheotomy care education for inpatient providers. This study aimed to assess the efficacy of this training program in improving trainee knowledge and comfort with tracheotomy care. Methods: The curriculum includes asynchronous online modules coupled with a self‐directed hands‐on simulation activity using a low‐cost tracheotomy care task trainer. The program was offered to inpatient providers including medical students, residents, medical assistants, nurses, and respiratory therapists. Efficacy of the training was assessed using pre‐training and post‐training surveys of learner comfort, knowledge, and qualitative feedback. Results: Data was collected on 41 participants. After completing the program, participants exhibited significantly improved comfort in performing tracheotomy care activities and 15% improvement in knowledge scores, with large effect sizes respectively and greater gains among those with little prior tracheotomy care experience. Conclusion: This study has demonstrated that completion of this integrated online and hands‐on tracheotomy simulation curriculum training increases comfort and knowledge, especially for less‐experienced learners. This training addresses an important gap in tracheotomy care education among health care professionals with low levels of tracheotomy care experience and ultimately aims to improve patient safety and quality of care. This curriculum is easily transferrable as it requires only access to the online modules and low‐cost simulation materials and could be used in other hospitals, long‐term care facilities, outpatient clinics, and home settings. Level of evidence: 4. Abstract : An accessible, easily transferrable tracheotomy care education program for inpatient providers was developed that includes asynchronous online modules coupled with a self‐directed hands‐on simulation activity using a low‐cost tracheotomy care task trainer. This study assessed the efficacy of the training program using pre‐training and post‐training surveys of learner comfort, knowledge, and qualitative feedback. After completing the program, participants exhibited significantly improved comfort in performing tracheotomy tasks and 15% improvement in knowledge scores, with large effect sizes respectively and greater gains among those with little prior tracheotomy care experience.